Alternative evolutionary strategies and tactics used by polyphagous insect to inhabit agricultural environment: Ostrinia nubialis as a case - Zhukovskaya, Marianna I.; Frolov, Andrey N. (Frontiers in Ecology and Evolution, 2022)
Substantial differentiation was found between Ostrinia populations, adapted to feed on dicotyledons and monocotyledonous host plants, which results not only in oviposition and larval survival differences but also in formation of ethological premating sex isolation mechanisms. Two strategies are surmised in warmer and colder areas, correspondingly: wide range of host plant species in combination with strict developmental stages of the plant, and alternatively, few host plant are infested during almost all the stages of their development, Inside these strategies, tactics are plastic. They are activated by the sensory stimuli, such as temperature, humidity and odorants. The tactic of dispersal flight before mating could be beneficial when the host plant is abundant, but mating before the flight is a better choice under the situation of sparse cornfields. There are still multiple questions to address for clear understanding of Ostrinia behavior and evolution.